E0553 Effect of pulmonary hypertension on the prognosis of patients with cardiac resynchronisation therapy. (17th November 2010) - Wang, Dongmei; Han, Yaling; Zang, Hongyun; Yan, Haibo; Zang, Donghong
Abstract : Introduction: There was a little of information about the effect of pulmonary artery hypertension to the clinical prognosis in patients with cardiac resynchronisation therapy (CRT). We aimed to investigate the effect of pulmonary artery systolic pressure (PASP) to the response of patients with CRT. Methods: 93 patients (76 male, mean ages: 61.23±15.56) with heart failure involved in our study. According to the level of preoperative PASP, they were divided into three groups (Group I: PASP ≥50 mm Hg, n=29; Group II: 30 mm Hg 0.05) and Group II (from 69 mm to 66 mm, p>0.05). LVEF increased averagely by 31–38% (p<0.01) in Group III at 3-6 months, But in Group I and II which had not obvious increased at 3 months (p>0.05) and had increased by 17% (Group I, p<0.05) and 26% (Group II, p<0.01)at 6 months. LVEF in Group III had increased more than that in Group I and Group II (p<0.05–0.01). Conclusions: Clinical outcomes post-CRT can be predicted by elevated PASP. A preoperative PASP ≥50 mm Hg is associated with increased risks for adverse events and a higher mortality for aggravation of heart function.